PENGEMBANGAN STANDAR DESAIN LAYANAN CLOUD BERDASARKAN ISO/IEC 20000: STUDI KASUS PT. XYZ - Ahmad Fikri Adriansyah; Bob Hardian; Gladhi Guarddin (Instruksional, 2020)
PT XYZ is now transforming its business from traditional telecommunication provider to an ICT (Information & Communication Technology) provider in order to deal with current stringent business competition. One of its strategic initiatives is to improve Cloud service market penetration based on the fact from market size analysis result which has reported that Cloud service would appear as an IT service with highest growth throughout Asia Pacific region from 2013 to 2018 (i.e., 49%). However, PT XYZ has reported its Cloud service sales only achieved 52% of its total revenue target in 2014 fiscal year. One of the root causes found is the lack of standard in performing design on Cloud service. As ISO/IEC 20000 certification holder, PT XYZ has to improve its IT service management practices continuously including its service design stage. This research goal is to build design standard on Cloud service in PT XYZ using two internationally recognized Information Technology Service Management (ITSM) frameworks, i.e. Information Technology Infrastructure Library (ITIL) version 3 and Microsoft Operation Framework (MOF) version 4, as well as Cloud Computing Reference Architecture (CCRA) and guidance on the application of ISO/IEC 20000-1 to Cloud Services (ISO/IEC TR 20000-9:2015). As the result, a design process flow and design documentation templates are proposed to be used as Cloud service design standard in PT XYZ.